Preventive effect of Lacticaseibacillus rhamnosus 2016SWU.05.0601 and its postbiotic elements on dextran sodium sulfate-induced colitis in mice - Bu, Linli; Li, Yang; Wang, Chen; Jiang, Yuhang; Suo, Huayi (Frontiers in Microbiology, 2024)
Microbial-based therapies are one of the hotspots in the field of ulcerative colitis research. The lactic acid bacteria and their postbiotics occupy a key position in microbial therapies, however, the mechanism by which they alleviate ulcerative colitis in mice is unknown. We investigated the effects of Lacticaseibacillus rhamnosus 2016SWU.05.0601 (Lr-0601) and its postbiotics on male Kunming mice with dextran sulfate sodium salt (DSS)-induced ulcerative colitis (UC). The results showed that Lr-0601 significantly alleviated the deterioration of UC and restored the expression of intestinal mechanical barrier proteins. In addition, Lr-0601 significantly reduced the expression of inflammatory cytokines in the body and regulated the expression of key regulatory genes of the NF-κB-iNOS/COX-2 signaling pathway in colon tissues to a large extent. Our results suggest that supplementation with Lr-0601 and its postbiotics can effectively prevent DSS-induced UC and have a beneficial effect on intestinal health, which also provides new insights and research bases for the prevention as well as the treatment of ulcerative colitis and other diseases related to intestinal barrier dysfunction and other diseases.